Manajemen Ekstrakurikuler Musik Islami Di SMKS Nurul Ulum Mangar Tlanakan Dan SMKS Nurus Salafiah Sejati Camplong - Muid, Abd (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Islamic music extracurricular activities (hadrah) in the learning environment play a crucial role in providing direct experience. Students actively participate and allocate sufficient time outside regular class hours, allowing education to be more accommodating through extracurricular activities. Therefore, proper management is necessary to ensure that Islamic music extracurricular activities (hadrah) run smoothly. Based on this premise, four main issues are analyzed in this study: First, how is the planning of Islamic music extracurricular activities at SMKS Nurul Ulum Mangar Tlanakan and SMKS Nurus Salafiah Sejati Camplong? Second, how is the organization of Islamic music extracurricular activities at these schools? Third, how is the implementation of Islamic music extracurricular activities at these schools? Fourth, how is the evaluation of Islamic music extracurricular activities at these schools?. This research adopts a qualitative approach with a descriptive research type. Data sources were obtained through interviews, observations, and documentation. The type of interview used was structured interviews, while non-participant observation was employed for observation. The research findings are as follows: (1) The planning of hadrah extracurricular activities at SMKS Nurul Ulum Mangar Tlanakan and SMKS Nurus Salafiah Sejati Camplong is conducted at the beginning of the academic year through meetings or discussions. (2) The organization of hadrah extracurricular activities involves determining responsibilities and identifying the necessary facilities and infrastructure. (3) The implementation of hadrah extracurricular activities begins with an introduction during the school orientation period (MPLS) for new students and the establishment of an organizational structure for the extracurricular activities. (4) The evaluation of hadrah extracurricular activities is carried out through meetings to assess and review the activities.